116k views
2 votes
4x - y = -4
5x = 2y +1
how do I solve this using elimination?

User Sorensen
by
5.6k points

2 Answers

5 votes
8x - 2y = -8
-5x + 2y = -1

3x = -9
x = -3
User RussellH
by
5.0k points
5 votes

Answer: x=-3, y=-8

Explanation:

you will leave the first equation alone for now

the second, we will subtract 2y from both sides

5x-2y=1

now you system is

4x-y=-4

5x-2y=1

we will multiply the first equation with -2

-8x+2y=8

5x-2y=1

add both equations, we get -8x+5x=9, -3x=9,

x=-3

we will replace x with -3 in any equation, lets use 4x-y=-4,

-12-y= -4, -y=12-4, -y=8, y=-8

User Lincoln Cheng
by
5.0k points